PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN DI SMK MA’ARIF 3 WATES - Forenza Eny Triatmaja; Arif Susanto; Aci Primartadi (STKIP Subang, 2026)
This study aims to improve student learning outcomes in Light Vehicle Engine Maintenance (PMKR) subject on the topic of Gasoline Fuel System through the implementation of the cooperative Jigsaw learning model in Class XI TKRO at SMK Ma’arif 3 Wates. This research employs a Classroom Action Research (CAR) design consisting of two cycles, each comprising planning, action, observation, and reflection stages. The subjects were 14 students. Data were collected through written tests and learning implementation observation sheets. The results showed that the average score increased from 55.36 (pre-cycle) to 73.57 (Cycle I) and 84.64 (Cycle II), while the classical completeness rate rose from 14.29% to 57.14% and finally 85.71%. The N-Gain values of 0.41 (Cycle I) and 0.44 (Cycle II) both fall in the moderate category. These findings confirm that the Jigsaw cooperative learning model effectively and consistently improves student learning outcomes in the PMKR subject on Gasoline Fuel System material.